Students’ Perspectives towards Cultural Representation in EFL Textbook Case of third-year students at Tamimi high school, M'sila - Lakhdari Khalissa, Aimeur Amira (UNIVERSITY MOHAMED BOUDIAF - M’SILA, 2021)
Abstract Teaching culture to EFL classes is a necessity of language proficiency; thus, it should appropriately be incorporated in a textbook. The present descriptive study is an attempt to investigate students’ perspectives toward cultural representation in the EFL textbook “New Prospect”. Moreover, this study attempts to analyse the way culture is presented and classified within the content of “New prospects” textbook. According to the research nature both qualitative and quantitative research methods were used in this study, data were collected through a questionnaire (quantitative research tool) that was delivered to 3rd secondary school Ibrahim ibn Al Aghlab Tamimi. Also, the content analysis technique (qualitative research tool) is used to analyse the cultural representation of two units in the “New Prospects” textbook (Unit one: Exploring the Past; Unit three: Schools: Different and Alike). The thoughtful analysis of the research findings indicate that students demonstrate a positive attitude toward the way culture is represented. However, student’s evaluation of the cultural content was superficial; thus content analysis technique is used to evaluate the cultural content of the “New Prospects” textbook and to assert the adequacy of the cultural aspects integrated into the EFL textbook, the result of the analysis showed that culture is giving little importance as an integral part of foreign language teaching, where it lacks to balance between the source culture and the target culture of the learners. The result of this study is significant to EFL textbook designers in the field of English language teaching by taking the student’s perspectives as an important element for developing the content of “New Prospects” in a way that meets student expectations and serves their need to accomplish intercultural competence. Key words:
Keywords: Key words: student’s perspectives, EFL textbook, cultural representation